2010
DOI: 10.2741/3625
|View full text |Cite
|
Sign up to set email alerts
|

A decade in search of myopia genes

Abstract: Nearly half of visual impairment in the world is caused by uncorrected refractive errors, and myopia constitutes a significant proportion of this problem. Moreover, the prevalence of myopia is increasing, especially in Asian countries. Linkage studies have identified at least 18 possible loci (MYP) in 15 different chromosomes associated with myopia, although some of these remain to be confirmed. However, when studies have been carried out to identify specific candidate genes, it is apparent that these genes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…The pathogenesis of high myopia is unknown. Twin studies have estimated high trait heritabilities, and genetic and environmental susceptibility factors have been demonstrated to play an important role in its development [11,12]. Myopic maculopathy describes a spectrum of clinical changes that comprise the main cause of visual loss among highly myopic individuals.…”
Section: Pathological Myopia -Prevalence and Pathogenesismentioning
confidence: 99%
“…The pathogenesis of high myopia is unknown. Twin studies have estimated high trait heritabilities, and genetic and environmental susceptibility factors have been demonstrated to play an important role in its development [11,12]. Myopic maculopathy describes a spectrum of clinical changes that comprise the main cause of visual loss among highly myopic individuals.…”
Section: Pathological Myopia -Prevalence and Pathogenesismentioning
confidence: 99%
“…Although there is evidence that refractive errors among siblings correlate closely,12 the genetic background of myopia remains unclear, as it may involve a complex interaction of multiple genes 13. Environmental associations have also been described between myopia and urban environment as well as with higher education 6…”
Section: Introductionmentioning
confidence: 99%
“…Instead of myopia being caused by a defect in a structural protein, defects in the control of these structural proteins might be the actual cause of myopia [81]. …”
Section: Pathological Myopiamentioning
confidence: 99%
“…Taken together, observational and experimental studies have revealed the complex nature of human refractive variation, which likely involves variants in several genes and functional pathways. Multiway interactions between genes and/or environmental factors may also be important in determining individual risks of myopia, and may help explain the complex pattern of refractive error in human populations [81]. …”
Section: Pathological Myopiamentioning
confidence: 99%